2023
DOI: 10.1108/ijqrm-03-2022-0095
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to supply chain performance measurement during disruptions such as the COVID-19 pandemic

Abstract: PurposeAmid the outbreak of coronavirus disease 2019 (COVID-19), supply chains have faltered. This has influenced operational and financial performance and lead to uncertainty in supply and distribution. Therefore, systems measuring supply chain risk and disruption management performance have gained interest. This study explores barriers to supply chain performance measurement during disruptions such as COVID-19.Design/methodology/approachBased on a survey and literature review, the authors formalise the barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…However, the use of supply chain management practices requires mutual adaption and consideration of the global context, and the requirements of the digital revolution (Khan, 2019;Mukherjee et al, 2023). The disruptive change experiences have highlighted the innovation in supply chain management practices, which require these issues to be addressed from a theoretical and a practical perspective (Altay & Pal, 2023;Fares et al, 2023;Gligor et al, 2018;Zinn & Goldsby, 2017). Supply chains play a pivotal part in the daily activities of enterprises and in global development (Garay-Rondero et al, 2020;Min et al, 2019) .…”
Section: Introduction Introductionmentioning
confidence: 99%
“…However, the use of supply chain management practices requires mutual adaption and consideration of the global context, and the requirements of the digital revolution (Khan, 2019;Mukherjee et al, 2023). The disruptive change experiences have highlighted the innovation in supply chain management practices, which require these issues to be addressed from a theoretical and a practical perspective (Altay & Pal, 2023;Fares et al, 2023;Gligor et al, 2018;Zinn & Goldsby, 2017). Supply chains play a pivotal part in the daily activities of enterprises and in global development (Garay-Rondero et al, 2020;Min et al, 2019) .…”
Section: Introduction Introductionmentioning
confidence: 99%
“…The fuzzy VIKOR, also known as the compromised ranking method, is used to find a compromised solution to the fuzzy multi-criteria problem. Existing studies have shown that combining these approaches provides more accurate ranking results (Opricovic, 2011; Solangi et al ., 2019; Fares and Lloret, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…While research on supply chain sustainability has made significant progress, there is a specific gap concerning the impact of interrelationships among e-commerce supply chain members [25][26][27]. Existing studies have predominantly focused on external factors, such as environmental regulations and supplier selection [26,28,29], overlooking the intricate dynamics and relationships within the supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…While research on supply chain sustainability has made significant progress, there is a specific gap concerning the impact of interrelationships among e-commerce supply chain members [25][26][27]. Existing studies have predominantly focused on external factors, such as environmental regulations and supplier selection [26,28,29], overlooking the intricate dynamics and relationships within the supply chain. This research aims to fill this gap by exploring the influence of interrelationships, including collaboration, communication, trust, and coordination, on the sustainability outcomes of e-commerce supply chains.…”
Section: Introductionmentioning
confidence: 99%